Developing brand identity for Aurora Park in Port Dickson / Nuratikah Husna Muhamad Nasir and Dona Lowii Madon - Muhamad Nasir, Nuratikah Husna; Madon, Dona Lowii (Kolej Pengajian Seni Kreatif (KPSK) UiTM Cawangan Melaka, 2023)
The purpose of this research is to understand the current issues of Aurora Park on the graphic design study in order to create a good brand identity. This is because they do not have a precise brand identity that can represent them as Aurora Park. Other than that, this research also aims to help Aurora Park stand out from other animal parks in Port Dickson and also to be comparable to zoos abroad that have a good brand identity. This research can help Aurora Park to get a good brand identity that can promote them as an animal park in Port Dickson. Furthermore, viewers can be more aware about the existence of Aurora Park Port Dickson. As a result, Aurora Park can be well-known not only in Port Dickson itself but also outside of the state. This is because Port Dickson is a tourist hot spot, so that it is easy for tourists to find out about Aurora Park. Tuah Centre.